|
สมัครสมาชิก | คู่มือการใช้ | รายชื่อสมาชิก | ปฏิทิน | ค้นหา | ข้อความวันนี้ | ทำเครื่องหมายอ่านทุกห้องแล้ว |
|
เครื่องมือของหัวข้อ | ค้นหาในหัวข้อนี้ |
#1
|
|||
|
|||
โจทย์เรขา ช่วยหน่อยนะครับ ข้อ 2
2. $\Delta ABC และ \Delta XYZ $ เท่ากันทุกประการ โดยมี $\propto จัตุรัส DEFB และ \propto จัตุรัส HIJK แนบใน \Delta ABC และ \Delta XYZ ตามลำดับ $
$\propto DEFB และ \propto HIJK มีพื้นที่ 441 และ 440 ตารางเมตร ตามลำดับ จงหาผลบวกของด้านประกอบมุมฉากของ \Delta ABC $ |
#2
|
||||
|
||||
อ้างอิง:
$$\frac{c-s}{s}=\frac{AD}{DE}=\frac{EF}{FC}=\frac{s}{a-s}\,.$$ That is, $$(c-s)(a-s)=s^2\,.$$ Thus, $$s=\frac{ac}{a+c}\,.$$ Now, let $r$ be the side length of the square $HIJK$. Note that $YZ=a$ and $XY=c$. Observe that $\triangle JYI\sim \triangle XYZ$. Therefore, $$\frac{JY}{r}=\frac{JY}{IJ}=\frac{XY}{ZX}=\frac{c}{\sqrt{a^2+c^2}}\,.$$ This means $JY=\dfrac{rc}{\sqrt{a^2+c^2}}$. Hence, $$XJ=XY-JY=c-\frac{rc}{\sqrt{a^2+c^2}}=c\,\left(1-\frac{r}{\sqrt{a^2+c^2}}\right)\,.$$ Now, $\triangle XKJ\sim \triangle XYZ$. That is, $$\frac{c}{\sqrt{a^2+c^2}}\,\left(1-\frac{r}{\sqrt{a^2+c^2}}\right)=\frac{XJ}{ZX}=\frac{JK}{YZ}=\frac{r}{a}\,.$$ Thus, $$r=\frac{ac}{a^2+ac+c^2}\,\sqrt{a^2+c^2}\,.$$ Now, observe that $$\frac{1}{s}=\frac{1}{a}+\frac{1}{c}\,,$$ making $$\frac{1}{s^2}=\frac{1}{a^2}+\frac{2}{ac}+\frac{1}{c^2}\,.$$ Thus, $$\frac{1}{s^2}=\frac{a^2c^2}{a^2+c^2}\,\left(\frac{1}{a^2}+\frac{1}{c^2}\right)\,\left(\frac{1}{a^2}+\frac{2}{ac}+\frac{1}{c^2} \right)\,,$$ whence $$\frac{1}{s^2}=\frac{a^2c^2}{a^2+c^2}\,\left(\frac{1}{a^4}+\frac{2}{a^3c}+\frac{2}{a^2c^2}+\frac{2}{ac^3}+\frac{1}{c^4}\right) \,.$$ We also have $$\frac{1}{r}=\frac{ac}{\sqrt{a^2+c^2}}\,\left(\frac{1}{a^2}+\frac{1}{ac}+\frac{1}{c^2}\right) \,,$$ so $$\frac{1}{r^2}=\frac{a^2c^2}{a^2+c^2}\,\left(\frac{1}{a^4}+\frac{2}{a^3c}+\frac{3}{a^2c^2}+\frac{2}{ac^3}+\frac{1}{c^4}\right) \,.$$ Consequently, $$\frac{1}{r^2}-\frac{1}{s^2}=\frac{a^2c^2}{a^2+c^2}\,\left(\frac{1}{a^2c^2}\right)=\frac{1}{a^2+c^2} \,.$$ That is, $$a^2+c^2=\frac{1}{\frac{1}{r^2}-\frac{1}{s^2}}=\frac{s^2r^2}{s^2-r^2} \,.$$ With $s^2=441\texttt{ m}^2$ and $r^2=440\texttt{ m}^2$, we obtain $$a^2+c^2=\frac{441\cdot 440}{441-440}\texttt{ m}^2=441\cdot 440\texttt{ m}^2=194040\texttt{ m}^2\,.$$ It can be shown that $(a,c)$ is a permutation of $$\left(231-63\sqrt{11}\texttt{ m},231+63\sqrt{11}\texttt{ m}\right)\,.$$ In general, $t=a$ and $t=c$ are the roots of the quadratic polynomial $$t^2-s\,\left(\frac{s+\sqrt{s^2-r^2}}{\sqrt{s^2-r^2}}\right)\,t+s^2\,\left(\frac{s+\sqrt{s^2-r^2}}{\sqrt{s^2-r^2}}\right)=0\,,$$ which are $$\frac{s}{2}\,\left(\frac{s+\sqrt{s^2-r^2}}{\sqrt{s^2-r^2}}\right)\,\left(1\pm\sqrt{1-\frac{4\sqrt{s^2-r^2}}{s+\sqrt{s^2-r^2}}}\right)\,.$$ From this result, we can see that $$r<s\leq \frac{3}{2\sqrt{2}}\,r\,.$$ The inequality on the right is an equality if and only if $a=c$. If $r=\dfrac{(1+u^2)(1+2u-u^2)}{1+2u+2u^2-2u^3+u^4}\,s$ for some parameter $u\in (0,1)$, then up to swapping, $$a=\frac{(2-u)(1+2u-u^2)}{2(1-u^2)}\,s$$ and $$c=\frac{1+2u-u^2}{2u(1-u^2)}\,s\,.$$ This parametrization is useful if we want to find a tuple $(a,c,r,s)\in\mathbb{Q}_{>0}^4$. For example, $u=\dfrac12$ and $s=444$ yield $$(a,c,r,s)=(777,1036,420,444)\,.$$ However, if you want to make $b:=CA=\sqrt{a^2+c^2}$ also a rational multiple of $s$, then you will need to solve the following Diophantine equation $$(2-u)^2u^2+1=v^2\,,$$ where $u$ and $v$ are rational numbers. So far, I only know that $(u,v)=\left(\dfrac12,\pm\dfrac54\right)$ and $(u,v)=\left(\dfrac{3}{2},\pm\dfrac54\right)$ are solutions to the equation above.
__________________
Потом доказывай, что ты не верблюд. 29 กรกฎาคม 2020 02:38 : ข้อความนี้ถูกแก้ไขแล้ว 17 ครั้ง, ครั้งล่าสุดโดยคุณ Anton |
เครื่องมือของหัวข้อ | ค้นหาในหัวข้อนี้ |
|
|